TITLE: DISCOURSE BETWEEN TEACHERS AND STUDENTS: A PEDAGOGICAL AND SOCIOCULTURAL EXPLORATION - Shamsutdinova Nazokat,; Mirzaazizova Farangiz, (TADQIQOTLAR, 2025)
Abstract: This article provides an in-depth analysis of the nature, function, and impact of discourse between teachers and students in educational settings. It explores how classroom communication influences students’ cognitive development, emotional well-being,  and  academic  performance.  The  paper  discusses  different  types  of classroom discourse, such as monologic, dialogic, and interactive discourse, and the role each plays in shaping the learning environment. Special emphasis is placed on sociocultural  influences,  the  power  dynamics  embedded  in  teacher-student interactions, and strategies for promoting effective, inclusive, and engaging dialogue. Drawing from contemporary research in linguistics, pedagogy, and psychology, the article underscores the critical role of discourse in fostering a democratic and learner-centered classroom culture.